THE EFFECT OF BLINDFOLD GAME ON STUDENTS’ VOCABULARY ACHIEVEMENT AT SMP NEGERI 13 KENDARI - Arfin, Andi An-Nisaa; Kamaluddin, Kamaluddin; Fatmawati, Wa Ode (Journal of Teaching of English, 2020)
The purpose of conducting this research is to examine the difference NGain scores between students who learn vocabulary with Blindfold Game and students who learn vocabulary without Blindfold Game at the first year students of SMP Negeri 13 Kendari. The samples of this research are the first grade four (VII-4) and the first grade three (VII-3) which consists of 27 students for each class. This research is conducted in comparison research design that consists of experimental class (VII-4) and controll class (VII-3). The data of this research are collected by giving pre-test and post-test in two classes (VII-4 & VII-3). The result shows that there is an improvement of the students’ vocabulary achievement. Independent samples t-test shows that, there is a significant difference in the Ngain scores for experimental class ( M = 60.08,  SD = 9.36 ) and controll class ( M = 20.41, SD = 14.56 ), t (52) = 11.904, p (0.000) < 0.05. Therefore, it can be concluded that the value of Sig (2 tailed) is lower than the significance α value (0.000 < 0.05). In other words, alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. It means that the Blindfold game can enrich students’ vocabulary achievement for Junior High School Student.